Dual-View Catadioptric Imaging System Design for Endoscopy - Wang, Chih Chung Roy (My University, 2010)
Fluorescence endoscopy is a promising functional imaging technique to improve screening of early cancer lesions in the gastrointestinal (GI) tract. The intensity of tissue autofluorescence is weak and conventional forward viewing endoscopes are inefficient in light collection from objects of interest located on the GI tract wall. This thesis work presents the design and optimization of a catadioptric endoscope objective lens that is capable of acquiring simultaneous forward and radial views. The radial view optics is optimized for a balance between image quality and light collection by utilizing a pair of folded parabolic mirrors for redirecting the field of view and lenses for aberration control. The modulation transfer function, numerical aperture, track length, and field of view are parameters used in the optimization. Non-sequential ray tracing simulations of the light collection of various field locations along a cylindrical surface that simulates the GI tract suggest that the proposed design is more practical in light collection when compared to typical wide-angle, forward-viewing endoscope objectives. A prototype with additional optimization in an enlarged 3:1 scale design is manufactured by the Instrument Technology Research Center of the National Applied Research Laboratories (Hsinchu, Taiwan, Republic of China). Empirical verification of the modulation transfer function as well as relative light collection across the field of view is performed on the manufactured prototype. View synthesis digital image processing algorithms are proposed and tested using imagery acquired by the manufactured prototype.
Keywords: Engineering Physics; Engineering Physics